Clinical significance and molecular mechanism of angiotensin-converting enzyme 2 in hepatocellular carcinoma tissues. Issue 1 (1st January 2021) - Huang, Wei-Jian; He, Wei-Ying; Li, Jian-Di; He, Rong-Quan; Huang, Zhi-Guang; Zhou, Xian-Guo; Li, Jian-Jun; Zeng, Da-Tong; Chen, Ji-Tian; Wu, Wei-Zi; Dang, Yi-Wu; Chen, Gang
ABSTRACT: During the pandemic of the coronavirus disease 2019, there exist quite a few studies on angiotensin-converting enzyme 2 ( ACE2 ) and SARS-CoV-2 infection, while little is known about ACE2 in hepatocellular carcinoma (HCC). The detailed mechanism among ACE2 and HCC still remains unclear, which needs to be further investigated. In the current study with a total of 6, 926 samples, ACE2 expression was downregulated in HCC compared with non-HCC samples (standardized mean difference = −0.41). With the area under the curve of summary receiver operating characteristic = 0.82, ACE2 expression showed a better ability to differentiate HCC from non-HCC. The mRNA expression of ACE2 was related to the age, alpha-fetoprotein levels and cirrhosis of HCC patients, and it was identified as a protected factor for HCC patients via Kaplan–Meier survival, Cox regression analyses. The potential molecular mechanism of ACE2 may be relevant to catabolic and cell division. In all, decreasing ACE2 expression can be seen in HCC, and its protective role for HCC patients and underlying mechanisms were explored in the study. Graphical Abtstract: uf0001